The type material of the Neotropical bee genus Habralictus Moure (Apidae, Halictinae) in the Museum für Naturkunde, Berlin, Germany - Gabriel A.R. Melo; Júlia Alberti de Liz (Papéis Avulsos de Zoologia)
Abstract The type material of species of Habralictus Moure, 1941 housed in the Museum für Naturkunde (ZMB), in Berlin, Germany, was studied, and lectotypes are designated for Neocorynura banghaasi Schrottky, 1910, Neocorynura ligea Schrottky, 1911 and Neocorynura metallica Friese, 1916. Taxonomic notes, diagnosis and redescriptions are presented. Remarks and photographs of the type specimens are also provided, including for Halictus xanthogastris Vachal, 1911.